2006
DOI: 10.1021/la0620354
|View full text |Cite
|
Sign up to set email alerts
|

Monomer Adsorption on Terraces and Nanotubes

Abstract: We construct a nonsparse transfer matrix (T-matrix) for a lattice gas model of monomers adsorbed on planar and nanotube surfaces of arbitrary geometry. The model can accommodate any number of higher-order pairwise adsorbate-adsorbate interactions. The technique is sufficiently general for application to nonequivalent adsorption sites and coadsorption of two or more monomer species. The T-matrices for monomer adsorption on a finite width terrace and for monomer adsorption on a nanotube, both of the same lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 75 publications
2
40
0
Order By: Relevance
“…In a number of very special cases, a method for computing the degeneracy relied on solving a number of linearly coupled recursion relations. Subsequently, we have shown that it is possible, in these special cases, to bypass the degeneracy problem and go directly to the partition function, replacing the problem of solving linearly coupled recursion relations by that of solving an equal number of linear equations among a set of generating functions. The linear equations are then solved using the standard matrix method, exhibiting the T matrix, whose eigenvalues provide the partition function, thus completely circumventing the degeneracy problem. Section 3 presents the generating function technique, which is now generalized to the coadsorption of n monomer species on terrace or nanotube surfaces of periodic geometry.…”
Section: General Formulation Of the Adsorption Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of very special cases, a method for computing the degeneracy relied on solving a number of linearly coupled recursion relations. Subsequently, we have shown that it is possible, in these special cases, to bypass the degeneracy problem and go directly to the partition function, replacing the problem of solving linearly coupled recursion relations by that of solving an equal number of linear equations among a set of generating functions. The linear equations are then solved using the standard matrix method, exhibiting the T matrix, whose eigenvalues provide the partition function, thus completely circumventing the degeneracy problem. Section 3 presents the generating function technique, which is now generalized to the coadsorption of n monomer species on terrace or nanotube surfaces of periodic geometry.…”
Section: General Formulation Of the Adsorption Problemmentioning
confidence: 99%
“…We follow an alternate path that does not rely on any approximation beyond that of the precision in conducting the numerical computations. This path is based on introducing generating functions. …”
Section: Partition Function and T Matrixmentioning
confidence: 99%
“…In addition, there is another reason why honeycomb lattices might be particularly interesting. From an experimental point of view, honeycomb lattices are intriguing systems, forming the structure of many natural and artificial objects [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Honeycomb lattices composed of carbon atoms form graphene sheets and carbon nanotubes [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental point of view, honeycomb lattices are intriguing systems, forming the structure of many natural and artificial objects [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Honeycomb lattices composed of carbon atoms form graphene sheets and carbon nanotubes [31][32][33][34][35][36][37]. The spontaneous formation of honeycomb structures has been observed in self-assembled layers of anthraquinone molecules on a Cu(111) surface [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The problem is not only of theoretical interest, but also has practical importance. A complete summary about adsorption on triangular lattices can be found in [12][13][14][15] and references therein.…”
Section: Introductionmentioning
confidence: 99%